Resources From Nerd to Wonk. - Patel-Predd, P. (IEEE spectrum)
The paper describes education programs which deal with engineering and policies that originated in United States. The programs train engineers to solve problems that lie at the junction of technology, society, and Politics. In addition to technical courses, the curriculum covers the methodologies of policy, economics, decision analysis, risk analysis and assessment, and management. Students learn to take big, messy, unstructured problems and then identify the most important pieces and ask the right questions.